Filling Up Your Pantry - Claudia Peñuela; Isabel Valentin-Oquendo (EDIS)
Revised! What is the best way to fill your pantry? It depends on what you like to eat and your style of cooking. Whatever your style, follow the suggestions in this 2-page fact sheet for filling up your pantry and freezer. It will help you be prepared and save time and money. Written by Claudia Peñuela and Isabel Valentin-Oquendo. Published by the UF Department of Family Youth and Community Sciences, June 2010.